2022
DOI: 10.1111/jvp.13085
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of carprofen in sheep

Abstract: The aim of this study was to determine the pharmacokinetics and bioavailability of carprofen in sheep following single intravenous (IV), intramuscular (IM), subcutaneous (SC), and oral (PO) administrations of a parenteral formulation at a dose of 4 mg/ kg. A total of eight sheep were used for the investigation. The study comprised four periods, according to a crossover design with a 21-day washout period between treatments. Plasma concentrations of carprofen were measured using HPLC-UV.Pharmacokinetic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…The t1/2λz of carprofen in CAST+CRP was found to be 41.59 h, which is consistent with recent findings in sheep (43.36 h) [27] and calves (43.4 h) [35]. Notably, this t1/2λz is longer than that reported for horse, cat, dog, and cows (8.00-30.7 h) [36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The t1/2λz of carprofen in CAST+CRP was found to be 41.59 h, which is consistent with recent findings in sheep (43.36 h) [27] and calves (43.4 h) [35]. Notably, this t1/2λz is longer than that reported for horse, cat, dog, and cows (8.00-30.7 h) [36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…Carprofen was well tolerated after single and repeated intravenous administration at a dose of 4 mg/kg to sheep [31,32]. It was reported that IV and extravascular (IM, oral, subcutaneous) t 1/2λz of carprofen in sheep were similar and peak plasma concentration was reached in 2.06-11.73 h after extravascular administration [27]. IV administration may be preferred for rapid onset of effect without absorption effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the t 1/2ʎz , Cl T and V dss of meloxicam after IV administration at 0.5 mg/kg dose were 10.33 h, 18.76 mL/h/kg and 247.10 mL/ kg, respectively. These data showed that meloxicam was eliminated slowly and had a low volume of distribution, similar to those previously reported in lambs and sheep (t 1/2ʎz , 10.85-14 h; Cl T , 10.20-16.00 mL/h/kg; V d , 180-320 mL/kg, Coskun, Corum, Durna Corum, Cetin, et al, 2023;Shukla et al, 2007;Stock et al, 2013). The low V d of meloxicam may be due to its high plasma protein binding, and ionization at physiological pH.…”
Section: Discussionsupporting
confidence: 87%
“…The plasma concentrations of meloxicam were assayed by high performance liquid chromatography (HPLC) with ultraviolet detection (UV) using a previous published method (Corum et al., 2022; Coskun, Corum, Durna Corum, & Uney, 2023). A total of 400 μL of methanol (0.1% formic acid) was added to 200 μL of plasma samples.…”
Section: Methodsmentioning
confidence: 99%